88.7k views
3 votes
What is the rule for the transformation below?

What is the rule for the transformation below?-example-1

1 Answer

5 votes

Answer: T(-5, 3)

=================================================

Step-by-step explanation:

The translation notation T(-5, 3) looks like an ordered pair point, but it is not. Instead, it is a rule to tell you how to shift any point left/right and up/down. The first number is the left/right shifting as its done along the x axis. The negative value means we shift left, so we shift 5 units to the left. The positive 3 in the y coordinate place means we shift 3 units up.

We see this shifting happen when we go from

  • A = (-1, -1) to A ' = (-6, 2)
  • B = (2, 3) to B ' = (-3, 6)
  • C = (5, -3) to C ' = (0, 0)

The translation notation T(-5, 3) is the same as writing
(x,y) \to (x-5, y+3) which may be a more descriptive notation to use, and it would avoid confusion with ordered pair point notation.

User Manjar
by
5.4k points